EFFECT OF THE CASCADE NEUTRALIZATION ENERGY ON THE SURFACE MODIFICATION BY THE IMPACT OF SLOW HIGHLY CHARGED IONS - Majkic, Milena; Nedeljković, Nataša; Mirković, Marko (Bulletin of Natural Sciences Research, 2019)
We consider the neutralization dynamics of slow highly charged ions in the interaction with a metal surface covered with a thin dielectric film from the standpoint of the surface modification. The quasi-resonant two-state vector model and the micro staircase model are used for the calculation of cascade neutralization energy for the ArZ+, KrZ+ and XeZ+ ions. The population of several ionic Rydberg states at each step of the neutralization cascade is demonstrated. The correlation between the neutralization and the potential energy is presented for moderate and very low ionic velocities and the relevance of this relation for the surface nanostructure formation is briefly discussed for a different angle of incidence and different dielectric materials.
Keywords: Metal-dielectric surface; Highly charged ions; TVM; Rydberg states; Collision geometry; Neutralization energy; Surface nanostructures